STRATEGI PEMERINTAH DALAM MEMINIMALISIR PERNIKAHAN DINI DI KECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - dahriah dahriah; Abdul Jabbar; Muhammad Rusdi (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
Motivated by the existence of problems regarding the rise of early marriage in the Maritengngae sub-district of Sidenreng Rappang district. The reason for the rise of early marriage in Maritengngae sub-district is the lack of socialization and government education about the dangers arising form early marriage. The factors that cause people to marry off their childern at an early age, namely : The desire to immediately get additional family members, matchmaking by parents or traditional factors, economic factors, educational factors, and Married by Accident (MBA) or pregnant outside of marriage.The research method used is descriptive qualitative research method to provide a clear picture of the problems studied in the Maritengngae district. The informant in this study is the purposive sampling method. There were 22 research informants, including 10 children married early, 5 parents who married their children at an early age, 3 village / kelurahan heads, maritengngae sub-district heads, religious court judges, 1 instructor of the National Population and Family Planning Agency (BKKBN), and Head of the Office of Religious Affairs (KUA) of the District of Maritengngae, Sidenreng Rappang Regency. Based on the results of the research in the field the researchers stated that the government's strategy in minimizing early marriage in the maritengngae sub-district of Sidenreng Rappang was not yet running optimally. This can be seen from the rise of early marriages that occur. And lack of understanding and education by the government to the community.